2010
DOI: 10.1111/j.1365-313x.2010.04385.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate systemically inhibits development of arbuscular mycorrhiza in Petunia hybrida and represses genes involved in mycorrhizal functioning

Abstract: SUMMARYMost terrestrial plants form arbuscular mycorrhiza (AM), mutualistic associations with soil fungi of the order Glomeromycota. The obligate biotrophic fungi trade mineral nutrients, mainly phosphate (P i ), for carbohydrates from the plants. Under conditions of high exogenous phosphate supply, when the plant can meet its own P requirements without the fungus, AM are suppressed, an effect which could be interpreted as an active strategy of the plant to limit carbohydrate consumption of the fungus by inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
321
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(349 citation statements)
references
References 101 publications
22
321
2
4
Order By: Relevance
“…The stability of older arbuscules against P inhibition was also suggested by other reports: P uptakes via AM fungi in the mycorrhizal roots of wheat (Triticum aestivum) and tomato (Solanum lycopersicum) treated with P were maintained, whereas colonization rates decreased (Li et al, 2006;Nagy et al, 2009). Breuillin et al (2010) reported that P did not reduce the colonization level of petunia mycorrhizal roots before 2 weeks after P supply, but the transcript levels of symbiotic P transporter genes were decreased within 2 d. It is possible that symbiotic P transporter proteins localize periarbuscular membranes to maintain arbuscules during P inhibition, but the transcription is immediately suppressed.…”
Section: P Treatment Selectively Inhibits the Development Of New Arbumentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of older arbuscules against P inhibition was also suggested by other reports: P uptakes via AM fungi in the mycorrhizal roots of wheat (Triticum aestivum) and tomato (Solanum lycopersicum) treated with P were maintained, whereas colonization rates decreased (Li et al, 2006;Nagy et al, 2009). Breuillin et al (2010) reported that P did not reduce the colonization level of petunia mycorrhizal roots before 2 weeks after P supply, but the transcript levels of symbiotic P transporter genes were decreased within 2 d. It is possible that symbiotic P transporter proteins localize periarbuscular membranes to maintain arbuscules during P inhibition, but the transcription is immediately suppressed.…”
Section: P Treatment Selectively Inhibits the Development Of New Arbumentioning
confidence: 99%
“…Low P uptake through direct pathways and increased P contents in mycorrhizal plants reflect superior P uptake via the mycorrhizal pathway. However, the application of inorganic P fertilizer has been shown to significantly reduce AM development in a number of studies (Baylis, 1967;Mosse, 1973;Sanders and Tinker, 1973;Breuillin et al, 2010;Balzergue et al, 2011) and is referred to as P inhibition (Graham et al, 1981). Given that mycorrhizal roots have higher P uptake under low P conditions, the formation of mycorrhizal symbiosis in the presence of high P conditions may also increase P uptake.…”
mentioning
confidence: 99%
“…High Pi availability enhances root growth and reduces the colonized versus non-colonized root length ratio (Smith et al 1992;Marschner 1995;. In addition, a very high Pi concentration can markedly modify root colonization, and reduce Pi uptake via the fungal pathway, arbuscule development, and the AM fungal biomass in both the roots and soil (Nagy et al 2009;Breuillin et al 2010;. High Pi conditions have also been shown to have an impact at the very early stages of the interaction with a dramatic decrease in hyphopodia formation (Balzergue et al 2011): this effect is probably due to a negative regulation of stimulatory compounds, such as strigolactones (Laparre et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since AM fungi also represent a carbon cost to the plant, it is of utmost importance to characterize and understand the molecular components involved in the mutual exchange of nutrients and their impact on plant physiology and productivity (Sawers et al 2008). While transcriptomics and genetics studies have provided convincing evidence that the AM fungus plays an important role in plant P and N uptake (Balestrini et al 2007;Javot et al 2007;Gomez et al 2009;Guether et al 2009a;Branscheid et al 2010) and indicate how the nutrient status of the plant influences AM development (Javot et al 2007;Yoneyama et al 2007;Nagy et al 2009;Breuillin et al 2010), information on the molecular components important for carbon transfer to the fungus and carbon metabolism in mycorrhizal plants remains rather patchy (Franken 2010). …”
Section: Introductionmentioning
confidence: 99%